The effect of postbiotics supplementation on obesity and metabolic health: a systematic review and meta-analysis of randomized control trials - Li, Shuwen; Sohouli, Mohammad Hassan; Li, Zeli (Nutrition & metabolism, 2025)
Background The prevalence of metabolic disorders such as obesity, type 2 diabetes, and dyslipidemia has increased globally. Postbiotics as non-viable microbial products or metabolites, have recently emerged as potential modulators of metabolic health due to their anti-inflammatory and insulin-sensitizing properties. In order to obtain a better viewpoint from them, this study aimed to comprehensively investigate the effects of postbiotics on metabolic health. Methods This systematic review and meta-analysis, adhering to PRISMA 2020 guidelines, synthesized data from 25 RCTs assessing the effects of postbiotic supplementation on metabolic parameters. Databases including PubMed, Embase, Web of Science, and Scopus were searched up to June 2025. Outcomes included glycemic indices, anthropometric measures, lipid profiles, inflammatory markers, and blood pressure. Results Postbiotic supplementation significantly reduced serum insulin levels (WMD: − 2.76 µU/mL), triglycerides (TG) (–8.46 mg/dL), waist circumference (WC) (–1.47 cm), and C-reactive protein (CRP) (–0.99 mg/L). However, changes in fasting blood glucose (FBG), homeostatic model assessment for insulin resistance (HOMA-IR), HbA1c, other profile lipids, blood pressure as well as weight and body mass index (BMI) were not statistically significant. Subgroup analyses revealed more pronounced benefits in younger participants, bacterial-based formulations, and interventions longer than 8 weeks. Risk of bias was low to moderate, and no major publication bias was detected. Conclusion Postbiotic supplementation demonstrates modest but clinically relevant benefits on insulin sensitivity, central adiposity, TG, and systemic inflammation. These effects suggest a promising adjunctive role for postbiotics in metabolic health interventions, though further trials with standardized formulations and longer durations are warranted.